2016
DOI: 10.1111/jgs.14518
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Medication‐Related Hospitalizations in Older Adults with Medication Management by Hospital and Community Pharmacists: A Quasi‐Experimental Study

Abstract: OBJECTIVES:To evaluate the association between a system of medication management services provided by specially trained hospital and community pharmacists (Pharm2Pharm) and rates and costs of medication-related hospitalization in older adults. DESIGN: Quasi-experimental interrupted time series design comparing intervention and nonintervention hospitals using a mixed-effects analysis that modeled the intervention as a time-dependent variable. SETTING: Sequential implementation of Pharm2Pharm at six general nonf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
110
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 17 publications
7
110
1
3
Order By: Relevance
“…The high rate of clinical acceptance of the pharmacists' interventions suggests that the patients' clinicians believed the recommendations were helpful. The decrease in readmission risk seen in our study is consistent with that seen in several studies involving pharmacist visits after hospital dismissal 3, 4, 5, 6, 7, 8. In contrast to these previous studies, we focused only on patients taking medications that confer a high risk of hospital admission.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high rate of clinical acceptance of the pharmacists' interventions suggests that the patients' clinicians believed the recommendations were helpful. The decrease in readmission risk seen in our study is consistent with that seen in several studies involving pharmacist visits after hospital dismissal 3, 4, 5, 6, 7, 8. In contrast to these previous studies, we focused only on patients taking medications that confer a high risk of hospital admission.…”
Section: Discussionsupporting
confidence: 89%
“…Because of their expertise in pharmaceutical care, pharmacists have had more opportunities to be involved in transitions of care to help prevent adverse drug events. Several initiatives involving pharmacist visits in primary care during care transitions have led to decreases in hospital readmission rates 3, 4, 5, 6, 7, 8. Expanding pharmacist involvement has the potential for substantial financial impact, given the potential for decreased reimbursement for higher 30-day readmission rates, per the Affordable Care Act of 2010.…”
mentioning
confidence: 99%
“…[30][31][32] We previously found that even patients treated with a palliative intent in our institution received an average of 40 doses of non-comfort medications in the week before their death or transfer to a palliative care unit. 4 Although we found only a modest reduction in direct medication costs in our population of patients nearing the end of life, other studies have shown the large potential financial costs of inappropriate prescription on a population scale, 15,16 and medication costs are often partially borne by patients themselves.…”
Section: Discussionmentioning
confidence: 56%
“…15,16 Deprescribing has been studied extensively in the general medical population, [17][18][19] but there is little published research on this approach in patients nearing the end of life. 20 Other medication-focused quality improvement initiatives have been broadly implemented, such as Antibiotic Stewardship 21 and Medication Reconciliation, 22 although they may not always improve patient care.…”
Section: Openmentioning
confidence: 99%
“…Although these results are disappointing, it is important to realize that patient education in the absence of comprehensive medication management is unlikely to considerably alter clinical outcomes for patients 7 . Pellegrin et al 8 completed a quasi-experimental, mixed methodology investigation designed to evaluate the association between medication management services provided by specially trained hospital and community pharmacists (ie, “Pharm2Pharm”) and rates and costs of medication-related hospitalization in older adults. The investigators concluded that the Pharm2Pharm model was associated with an estimated 36% reduction in the medication-related hospitalization rate for older adults and a 2.6 to 1 return on investment 8 .…”
mentioning
confidence: 99%